2013
DOI: 10.1371/journal.pone.0078359
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Periodic Leg Movement During Sleep Is an Unrecognized Risk Factor for Progression of Atrial Fibrillation

Abstract: Sleep apnea has been recognized as a factor predisposing to atrial fibrillation recurrence and progression. The effect of other sleep-disturbing conditions on atrial fibrillation progression is not known. We sought to determine whether frequent periodic leg movement during sleep is a risk factor for progression of atrial fibrillation. In this retrospective study, patients with atrial fibrillation and a clinical suspicion of restless legs syndrome who were referred for polysomnography were divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 47 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…Fibers were mechanically separated along the longitudinal axis and permeabilized with saponin (30 -50 g/ml) for 30 min at 4°C. After permeabilization, myofibers were washed in ice-cold buffer containing (in mM) 110 K-MES (pH 7.4), 35 KCl, 1 EGTA, 5 KH2PO4, and 3 MgCl2·6H2O, and 0.02 blebbistatin with 5 mg/ml BSA and remained in the buffer until analysis at 4°C.…”
Section: Separation and Identification Of Mitochondrial Oxidative Phomentioning
confidence: 99%
See 1 more Smart Citation
“…Fibers were mechanically separated along the longitudinal axis and permeabilized with saponin (30 -50 g/ml) for 30 min at 4°C. After permeabilization, myofibers were washed in ice-cold buffer containing (in mM) 110 K-MES (pH 7.4), 35 KCl, 1 EGTA, 5 KH2PO4, and 3 MgCl2·6H2O, and 0.02 blebbistatin with 5 mg/ml BSA and remained in the buffer until analysis at 4°C.…”
Section: Separation and Identification Of Mitochondrial Oxidative Phomentioning
confidence: 99%
“…The incidence and prevalence of AF increase with advancing age and aging-associated diseases such as hypertension, ischemic heart disease, and heart failure (2, 40) and contribute to increased morbidity, particularly an increased risk for stroke, heart failure, and death (25,52). Although the pathophysiology of AF has been well characterized, the underlying mechanisms that contribute to the progression of AF in human atria have not been fully defined (33,35,57,58,60). Mitochondria, occupying 30% of cardiomyocyte volume, are critical for maintaining normal energetics of the heart, a highly aerobic organ dependent on oxidative phosphorylation (OXPHOS) for maintenance of its normal electrical and mechanical function (1, 61).…”
mentioning
confidence: 99%
“…However, the mean apnea/hypopnea index (AHI) was similar between the two groups. 51 In a cross-sectional study of 2,793 community-dwelling older men, Koo et al found no significant associations between PLMI and PLM arousal index with ventricular or atrial arrhythmias (after adjusting for potential confounders). 50 In summary, there are limited data between the association of PLMS and arrhythmias.…”
Section: Rls/plms and Arrhythmiasmentioning
confidence: 96%
“…50,51 Sleep disruption due to other sleep disorders has been associated with increased prevalence of arrhythmias, including sleep apnea and insomnia. 52,53 This review presents the evidence concerning RLS/PLMS and heart arrhythmias.…”
Section: Rls/plms and Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation